Development and application of LAMP assays for the detection of enteric adenoviruses in feces - Anna K. Shuryaeva; Tatyana V. Malova; Anna A. Tolokonceva; Sofia A. Karceka; Maria A. Gordukova; Ekaterina E. Davydova; German A. Shipulin (Microbiology Spectrum, 2022)
ABSTRACT Loop-mediated isothermal amplification (LAMP) is an alternative to PCR that is faster and requires fewer resources. Here, we describe two LAMP assays for the detection of human adenoviruses in the feces of children with acute intestinal infections. We designed сolorimetric LAMP (c-LAMP) and real-time LAMP (f-LAMP) with fluorescent probes to detect the DNA of the adenovirus F human adenovirus 40/41 (hAdV40/41) hexon gene. The detection limit of both developed methods was 103 copies/mL, which is comparable to the sensitivity of PCR. The specificities of both c-LAMP and f-LAMP were high, with no false-positive results for clinical samples that do not contain adenovirus F, when testing other viruses and microorganisms. Comparative tests of PCR and LAMP on clinical samples from patients with acute gastroenteritis were carried out. For all samples with a PCR threshold cycle (CT) of up to 36, the PCR and LAMP results completely coincided; however, at low viral loads, the diagnostic sensitivity of LAMP, especially c-LAMP with colorimetric detection, was inferior to that of PCR. The combination of LAMP with modern methods of nucleic acid extraction, both in manual and automatic modes, can reduce the time for a complete study, including extraction of nucleic acid material and amplification, to 60 min. IMPORTANCE In April 2022, several cases of acute hepatitis of unknown origin were reported in children from 12 countries. In many cases, enteric adenovirus or SARS-CoV-2 and adenovirus coinfection were detected. It is known that human adenoviruses can cause different infections of varying severity, from asymptomatic to severe cases with lethal outcomes. There is a need to increase the diagnostic capabilities of clinical laboratories to identify such an underestimated pathogen as adenovirus. Although PCR remains the gold standard for pathogen detection, this method requires specialized equipment and has a long turnaround time to process samples. Previously, LAMP assays for the detection of human adenovirus have been based on measuring the turbidity, the fluorescence of intercalated dyes, or electrophoretic separation. Herein, we present LAMP-based assays with colorimetric or fluorescent detection and perform a detailed assessment of their sensitivity, specificity, and diagnostic performance.